2015
DOI: 10.1111/nbu.12178
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking paradigms for studying mechanisms of action of plant bioactives

Abstract: Many foods in our diets such as berries, tea, chocolate and wine contain flavonoids, which are natural components of plants. A substantial body of evidence supports the role of flavonoids in providing protection against cardio-metabolic diseases and disorders. Despite the nearly exponential growth in flavonoid research in the past 20 years, limited progress has been made in understanding how these dietary components work. Research initially focused on their antioxidant activity without taking into account thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In words of Kay [152], 'These studies on (flavonoid) metabolism and biological activity of metabolites mark a new beginning in phytochemical research and, in this respect, this work is in its infancy'. Phenol-Explorer web database gathers polyphenol metabolites [153] identified in human and animal biofluids, from 221 publications.…”
Section: Flavonoids -From Biosynthesis To Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In words of Kay [152], 'These studies on (flavonoid) metabolism and biological activity of metabolites mark a new beginning in phytochemical research and, in this respect, this work is in its infancy'. Phenol-Explorer web database gathers polyphenol metabolites [153] identified in human and animal biofluids, from 221 publications.…”
Section: Flavonoids -From Biosynthesis To Human Healthmentioning
confidence: 99%
“…A multicompartmental (theoretical physiologically based) pharmacokinetic (PBMK) model has been proposed [138] in order to describe the anthocyanins fate in vivo. Understanding the elimination kinetics of these metabolites is key to the design of future studies [152] concerning with their utility in dietary intervention or as therapeutics for disease risk reduction.…”
Section: Flavonoids -From Biosynthesis To Human Health 212mentioning
confidence: 99%
“…A recent study attempted to account for the fate of the remaining 99% of ingested anthocyanins that are not recovered in blood and urine. Rather than confirm that anthocyanins had low bioavailability resulting from poor absorption and chemical instability , the study identified an extensive biotransformation of anthocyanins that resulted in a relative bioavailability (i.e. the amount absorbed and found in blood, urine and breath) of 12%, rather than the previously assumed 1%.…”
Section: Discussionmentioning
confidence: 99%
“…An aspect of many of the papers in this issue of Nutrition Bulletin is the requirement for robust evidence if claims are to be made linking a nutrient, food or ingredient of a food with a particular beneficial effect. Examples include papers on fluoride (Ruxton & Bond ), vitamin D (Buttriss ), fibre (Buttriss ), plant bioactives (Kay ) and, in particular, a paper that describes an EC‐funded project ( REDICLAIM ) that aims to understand the impact of European Regulation on the substantiation and use of new general claims and ‘reduction of disease risk’ claims in foods and drinks (Raats et al . ).…”
mentioning
confidence: 99%